2016
DOI: 10.1590/1809-98232016019.160026
|View full text |Cite
|
Sign up to set email alerts
|

Home-based oral healthcare strategies of elderly people with Alzheimer's disease

Abstract: Objective: To identify strategies used in the oral health care of elderly persons with Alzheimer's disease in the home. Method: an exploratory, descriptive study with a qualitative approach to collecting and analyzing data was performed. Data was collected through interviews with 30 caregivers and analyzed by the content analysis technique. Results: The majority of subjects were female, daughters of the elderly person, university graduates and aged 32-77 years. The strategies identified were grouped into categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…The profile of the caregiver obtained on this study was similar to the one found on literature 4,6 . They are informal caregivers, It is necessary to emphasize that, in the case of the evaluated elderly, the use of superior prothesis was higher than the inferior ones, and it did not necessarily correspond to a higher jaw edentulism.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The profile of the caregiver obtained on this study was similar to the one found on literature 4,6 . They are informal caregivers, It is necessary to emphasize that, in the case of the evaluated elderly, the use of superior prothesis was higher than the inferior ones, and it did not necessarily correspond to a higher jaw edentulism.…”
Section: Discussionsupporting
confidence: 87%
“…When the elderly loses the ability to feed itself, in most cases, it also cannot perform oral hygiene cares. In these cases, the caregivers are the main providers, and the planning of the oral health care depends on the perception of these caregivers and their knowledge of oral health and hygiene 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that self-perception may contribute to the direction and planning of dental services 19,20, contrary to the results presented herein since self-perception was positive even in the presence of precarious clinical conditions. This may be because most elderly people (and also their caregivers and family members) tend to consider oral issues secondary to other systemic problems 9,21.…”
Section: Discussionmentioning
confidence: 99%
“…The aging process makes the human being more susceptible to chronic diseases of progressive character, as is the case of Alzheimer's disease (AD), which is responsible for approximately 50 to 75% of dementias in several countries 1 . In Brazil, it is estimated that one million people are affected by AD; however, there is still not much data regarding its incidence in the country 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Public policies, in the context of the health of old people, recommend the use of creative strategies that favor communication between professional, subject and group 5 . Thus, some professionals, teaching and health institutions have invested efforts in the context of Gerontology, in the understanding and use of gerontotechnological possibilities 6 .…”
Section: Introductionmentioning
confidence: 99%